2012
DOI: 10.1093/neuonc/nos158
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma resistance to anti-VEGF therapy is associated with myeloid cell infiltration, stem cell accumulation, and a mesenchymal phenotype

Abstract: Vascular endothelial growth factor (VEGF) is a critical regulator of angiogenesis. Inhibiting the VEGF-VEGF receptor (R) signal transduction pathway in glioblastoma has recently been shown to delay progression, but the relative benefit and mechanisms of response and failure of anti-VEGF therapy and VEGFR inhibitors are not well understood. The purpose of our study was to evaluate the relative effectiveness of VEGF sequestration and/or VEGFR inhibition on orthotopic tumor growth and the mechanism(s) of treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
194
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(206 citation statements)
references
References 42 publications
10
194
0
2
Order By: Relevance
“…It is currently a matter of intense investigation if TAM can mediate resistance to Bevacizumab by releasing angiogenic factors alternatively to VEGF-A. Myeloid cells accumulating in GBM can promote the acquisition of a mesenchymal tumour-subtype [84,38,34], which is associated with resistance to Bevacizumab [114,115]. However, as with most pathways controlled by TAM, support of angiogenesis is only one side of the intra-tumoural actions of these immune cells in gliomas.…”
Section: The Pro-angiogenic Role Of Myeloid Cells In Gliomasmentioning
confidence: 99%
“…It is currently a matter of intense investigation if TAM can mediate resistance to Bevacizumab by releasing angiogenic factors alternatively to VEGF-A. Myeloid cells accumulating in GBM can promote the acquisition of a mesenchymal tumour-subtype [84,38,34], which is associated with resistance to Bevacizumab [114,115]. However, as with most pathways controlled by TAM, support of angiogenesis is only one side of the intra-tumoural actions of these immune cells in gliomas.…”
Section: The Pro-angiogenic Role Of Myeloid Cells In Gliomasmentioning
confidence: 99%
“…A previous study from our group found that anti-VEGF-A therapy increases invasive properties both in a GBM stem cell line (GSC11) and in glioma U87 xenograft tumors 4 . By using microarray analysis we found several genes including POSTN that were upregulated in bevacizumab resistant tumors.…”
Section: Introductionmentioning
confidence: 85%
“…Recently, we reported that the glioma treated with bevacizumab have higher periostin (POSTN) expression than control tumors in a murine glioma tumor models 3 . In this commentary, we review our recent findings as well as the role of POSTN in antiangiogenic therapy resistance in glioma.A previous study from our group found that anti-VEGF-A therapy increases invasive properties both in a GBM stem cell line (GSC11) and in glioma U87 xenograft tumors 4 . By using microarray analysis we found several genes including POSTN that were upregulated in bevacizumab resistant tumors.…”
mentioning
confidence: 85%
“…obtained only from pre-clinical models using breast cancer cell lines [12][13] , or glioma cell lines [14] . Thus, using these patient-derived renal cell carcinoma xenografts, we have shown that the number of renal cancer stem cell is directly linked to the percentage of necrosis in the tumor.…”
Section: Research Highlightmentioning
confidence: 99%